The Influence of Perception Regarding Startup Towards Career Choices in Startup Field on Generation Y and Generation Z College Students in Bandung City - Sarah Sentika; Rivaldi Arissaputra (CV. AFDIFAL MAJU BERKAH, 2021)
The importance of the development of startups in Indonesia to help the digital economy provides opportunities for generation Y and Z students to contribute considering that there are similarities in the work scope between startups and generations Y and Z. However, their tendency to change jobs is a challenge in making choices. suitable career. The purpose of this study was to examine and analyze the effect of perceptions about startups on career choices in the startup field for generation Y and Z students in Bandung. The sample in this study as many as 168 respondents were taken using the accidental sampling method and processed using SmartPLS 3. The results showed that in generation Y and generation Z perceptions about sta rtups had a significant effect on career choices in the startup field, but if they were differentiated by group, the generation Y perception about startups has an influence on career choices in the startup field, while in the generation Z group perceptions about startups have no effect on career choices in the startup field.